Некоторые особенности экологии яблонной плодожорки (Carpocapsa pomonella L.), зимующей в почве - Гродский, В.А.; Руднев, Д.Ф. (Вестник зоологии, 1970)
There are contradictory data in the problem of Carpocapsa pomonella L. caterpillar place of pupation and wintering.
As a result of investigations, carried out in 1964—1965 in the gardens of Zaporozhitr region of the Ukraine, it was established that in the Steppe zone of the Ukraine caterpillars hibernate not only on the trees but also in soil (27—36%), both in cultivated and uncultivated one; the main quantity of caterpillars in soil (43—57%) are arranged near the root collar, 26—29% of caterpillars — at a distance up to 0.5 m from the trunk. Cocoons lie in the soils at the depth of 1—5 cm; the death rate of caterpillars, wintering on trees, froth entomophages and unfavourable conditions reaches 35% whereas in soil the caterpillars are almost completely preserved.
So, soil is a very favourable place for wintering of coterpillars of Carpocapm pomonella L.